2017
DOI: 10.1016/j.conbuildmat.2017.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grinding on early age performance of high volume fly ash ternary blended pastes with CKD & OPC

Abstract: 8This study investigated setting times and early age compressive strength of the high volume fly ash (HVFA) blended 9 pastes prepared with ground materials. The pastes consisted of 60% Fly Ash + 30% Portland cement (CEM I) + 10% 10 cement kiln dust (CKD) and tests were carried out for four different fly ashes. In phase 1, all the constituent binder 11 materials (class F-fly ash, CEMI and CKD) were initially mixed in the relevant proportions and were ground for 12 varying time periods (1, 2 and 4 hours). In pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
(1 reference statement)
1
7
0
Order By: Relevance
“…It may be the effect of better homogeneity. The advantages of intergrinding on separate grinding of the components were also reported by other researchers [73]. Jaturapitakkul et al [79] Influence of selected activating methods on hydration processes... reaction and densification of the structure.…”
Section: Mechanical Activationmentioning
confidence: 76%
See 2 more Smart Citations
“…It may be the effect of better homogeneity. The advantages of intergrinding on separate grinding of the components were also reported by other researchers [73]. Jaturapitakkul et al [79] Influence of selected activating methods on hydration processes... reaction and densification of the structure.…”
Section: Mechanical Activationmentioning
confidence: 76%
“…There are publications discussing effectiveness of this type of activation depending on different factors, such as the kind of fly ash, the way of grinding of dry constituents (separately or intergrinding), using grinding aids, time of grinding, as well as time and temperature of hardening of composites performed with mechanically activated materials, etc. [11,65,69,73,74,78]. For example, Kumar et al [69] concluded that 50-60% of mechanically activated fly ash can be used as clinker replacement and such blended cement exhibits compressive strength and other properties comparable to commercial cement.…”
Section: Mechanical Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used cements containing fly ash, slag, pozzolans and other components are commercially available [3]. Nowadays, binding ''green'' mixtures containing ecologically friendly non-clinker components arouse interest and they are the subject of research works, e.g., [4][5][6][7][8][9]. Some industry byproducts can be used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of fly ash used as replacement of cement usually does not exceed 35%. However, composites containing much higher quantity of fly ash in the binding material arouse interest [8,[10][11][12][13][14][15]. Portland cement in lowcement mixtures acts as hydraulic component and activator for fly ash.…”
Section: Introductionmentioning
confidence: 99%